A survey of music therapists' attitudes toward evidence-based practice - Hahn, Kevin, author; LaGasse, A. Blythe, advisor; Davis, William B., committee member; Henle, Chris, committee member (Colorado State University. Libraries, 2013)
Background: Evidence-based practice is the confluence of research evidence, practitioner expertise, and client preferences applied in a clinical context. An expansion of the evidence-based medicine movement developed during the early 1990s, evidence-based practice (EBP) has garnered significant attention from healthcare researchers, academics, and clinicians through the alternating endorsement and criticism it receives. Opinions about EBP are likely to vary greatly within a given field, yet little research has been completed to systematically investigate how music therapists view EBP. Given the American Music Therapy Association's inclusion of "evidence-based" in the definition of music therapy, a lack of recent, systematically-gathered information about music therapists' perceptions of EBP highlights the question: What are music therapists' attitudes toward evidence-based practice? Objective: The primary purpose of this study was to survey professional music therapists' attitudes toward evidence-based practice (EBP). This study also sought to determine how music therapists' attitudes toward evidence-based practice systematically vary based on familiarity with EBP, age, year entering the field, years of experience, level of formal academic training, primary philosophical orientation, and additional music therapy designations. Methods: Board-certified music therapists (MT-BCs) were surveyed using a 26-item measure of attitudes toward evidence-based practice (adapted from Johnston et al., 2003). After giving informed consent, participants were provided with a definition of EBP and then completed the adapted Johnston et al. (2003) measure, answered additional items measuring the strength of their attitudes toward EBP, and supplied demographic and professional status information. A total of 646 participants provided results included in the final dataset. Results: On a scale from 1 (lowest) to 6 (highest), 646 participating MT-BCs indicated a mean average response of 4.31 (SD = .65) on an adapted scale of attitudes toward evidence-based practice. Participants reported a mean level of familiarity with EBP of 5.11 (SD = 1.35, n = 643) on a scale from 1 (very unfamiliar) to 6 (very familiar). Familiarity with EBP was positively correlated with and predicted attitudes toward EBP. Participants' age in years and calendar year entering the profession were associated with attitudes toward EBP. Participants' attitudes toward EBP differed based on primary philosophical orientation, level of training, and additional training designations. Conclusions: Responses from this study suggest MT-BCs are very familiar with evidence-based practice and possess generally favorable attitudes toward EBP. Increasing music therapists' familiarity with EBP may predict a moderate increase in their attitudes toward EBP (adjusted r2= .057). Instrument revision and study replication are recommended due to methodological and sampling concerns. Music therapists' supportive attitudes toward EBP might indicate their willingness to engage in EBP in clinical practice.
Keywords: clinical decision-making; music therapy; evidence-based practice; evidence-based medicine